MOTION GRAPHIC MITIGASI BENCANA GEMPA BUMI UNTUK ANAK SD DI KOTA PADANG - KIKI ARINDI, Dini Faisal, S.Ds., M.Ds., Hendra Ariwan, S.Sn., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The purpose of this design is to optimize learning about earthquake disaster mitigation for elementary school children in the city of Padang, through audio-visual media based on motion graphics. Because the city of Padang is a region that has a high potential for earthquakes in Indonesia, it must be balanced with adequate preparedness understanding and training. This design produces audio visual media in the form of motion graphics that contain earthquake risk reduction or mitigation. Besides this design is also supported by several other media such as: CD Cover, CD Label, Infographic Poster, Notebook, Banner, T-shirt, Hat, and Sticker. The design method used in this design is a meode glass box which is a rational and logical design, and through several stages considered by the designer.Keywords : Motion Graphic, Earthquake, Padang